2011
DOI: 10.1111/j.1600-0714.2011.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐syndromic multiple supernumerary teeth: meta‐analysis

Abstract: Although NSMST is a condition that has a higher incidence in the male gender, no differences have been found as to their number and localization in both genders. Bilaterality seems to be a common characteristic of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…This pathogenetic hypothesis can also be supported by the sporadically reported simultaneous presence of ODs and SPNs in non-syndromic cases 13 , 26 , 53 , 56 , 151 - 153 and by many cases of non-syndrome multiple (more than five) SPNs. 154 - 156 Moreover, CxODs and supernumerary microdontic teeth have been alternatively found in Otodental Dysplasia, 122 an autosomal dominant inherited condition whose locus has been mapped to 20q13.1 within a 12-cM critical chromosomal region, 157 and a CxOD has been found as well in association with 1 SPN in a variant of Ekman-Westborg-Julin Syndrome. 105 …”
Section: Discussionmentioning
confidence: 99%
“…This pathogenetic hypothesis can also be supported by the sporadically reported simultaneous presence of ODs and SPNs in non-syndromic cases 13 , 26 , 53 , 56 , 151 - 153 and by many cases of non-syndrome multiple (more than five) SPNs. 154 - 156 Moreover, CxODs and supernumerary microdontic teeth have been alternatively found in Otodental Dysplasia, 122 an autosomal dominant inherited condition whose locus has been mapped to 20q13.1 within a 12-cM critical chromosomal region, 157 and a CxOD has been found as well in association with 1 SPN in a variant of Ekman-Westborg-Julin Syndrome. 105 …”
Section: Discussionmentioning
confidence: 99%
“…( 18 ) studied 303 supernumerary teeth in 200 patients observing that 88% were situated in the upper maxilla. However, another study of 393 supernumerary teeth found almost the same frequency in the two jaws ( 23 ).…”
Section: Prevalencementioning
confidence: 94%
“…Several theories have been proposed to explain their occurrence. The most common are phylogenetic theory; an abnormal reaction to a traumatic local event; environmental factors; the dichotomy of the tooth germ; and the theory of hyperactivity of the dental lamina [12]. The last one seems to be the more accepted [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Heredity is considered to be an important factor, especially in the development of multiple supernumerary teeth, which are considered to represent a partial third dentition in humans. Their inheritance however does not seem to follow a Mendelian pattern [2, 12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation